2013
DOI: 10.1007/s00421-012-2583-6
|View full text |Cite
|
Sign up to set email alerts
|

The angiotensin converting enzyme insertion/deletion polymorphism alters the response of muscle energy supply lines to exercise

Abstract: The presence of a silencing sequence (the I-allele) in the gene for the upstream regulator of blood flow, angiotensin I-converting enzyme (ACE), is associated with superior endurance performance and its trainability. We tested in a retrospective study with 36 Caucasian men of Swiss descent whether carriers of the ACE I-allele demonstrate a modified adaptive response of energy supply lines in knee extensor muscle, and aerobic fitness, to endurance training based on 6 weeks of supervised bicycle exercise or 6 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
0
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(80 citation statements)
references
References 42 publications
4
70
0
6
Order By: Relevance
“…More recently, we have shown ACE-I/D dependent responses of serum levels of angiotensin 2 and capillary perfusion to intense cycling exercise [8]. These results suggest a critical role of ACE-modulated vascular tone, which is important for the regulation of response to exercise [13,12]. test, breath-by-breath respiratory data were collected using a calibrated spirometry system (JAEGER Oxycon alpha, CareFusion, Höchberg, Germany) and heart rate was monitored using a heart rate chest belt (Accurex Plus, Polar Electro Oy, Kempele, Finland).…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…More recently, we have shown ACE-I/D dependent responses of serum levels of angiotensin 2 and capillary perfusion to intense cycling exercise [8]. These results suggest a critical role of ACE-modulated vascular tone, which is important for the regulation of response to exercise [13,12]. test, breath-by-breath respiratory data were collected using a calibrated spirometry system (JAEGER Oxycon alpha, CareFusion, Höchberg, Germany) and heart rate was monitored using a heart rate chest belt (Accurex Plus, Polar Electro Oy, Kempele, Finland).…”
Section: Introductionmentioning
confidence: 80%
“…It was therefore suggested that several processes downstream of ACE activity contribute to elevated endurance performance and trainability in subjects carrying the ACE I-allele [10,11]. In this context, we recently identified an ACE I-allele dependent up-regulation of muscle transcripts associated with glucose and lipid metabolism during recovery from endurance exercise [12]. Additionally subjects carrying at least one I-allele, were found to show reduced capillarity at rest, but amplified mitochondrial biogenesis after cycling-type endurance exercise.…”
Section: Introductionmentioning
confidence: 93%
“…All of these relate to metabolic fitness. This is shown for genotyping of the ACE I/D polymorphism based on mucosal samples, as well as for the quantification of changes in angiotensin 2, arterial oxygen saturation, serum lactate and glucose in blood serum after a maximal aerobic workout [28,38,41]. While the prospective power and robustness of these molecular candidates as biomarkers for muscle performance and its malleability remains to be evaluated; the current data indicate that the step from diagnosis to prognosis may be in close reach.…”
Section: Translating Basic Sciences In Diagnostic Practice -Research mentioning
confidence: 99%
“…Towards this end we recently pointed out that exercise-induced transcript expression provides a mechanistic connection between heritable factors and inter-individual variability in the phenotypic response to endurance exercise [38]. The investigation shows that the polymorphism for a 287bp gene insertion in intron 16 (the I-allele) of the gene for the producer of the major vasoconstrictor angiotensin 2, angiotensin-converting enzyme (ACE), affects plasticity of aerobic metabolism in skeletal muscle.…”
Section: Limitations In Current Performance Testing -A Major Drawbackmentioning
confidence: 99%
See 1 more Smart Citation